Alignment of Pharmacotherapy Course Assessments With Course Objectives - Wittstrom, Kristina (American Journal of Pharmaceutical Education, 2010)
OBJECTIVE: To determine whether instructor-prepared classroom examinations for pharmacotherapy courses were aligned with course goals and objectives. DESIGN: Assessment items from examinations in 2 pharmacotherapy courses were evaluated. Four categories of alignment (depth of knowledge, categorical concurrence, range of knowledge, and balance of representation) were used to match course assessments with objectives. ASSESSMENT: While assessments met the criteria for acceptable alignment, there were areas for improvement. Goals and objectives were unevenly assessed, with 1 goal aligning with 45% of all assessment items. The assessments covered all content categories and the range of knowledge established by the objectives, but objectives under specific goals were not evenly assessed. CONCLUSION: This alignment study provided quantitative data useful for review and revision of pharmacotherapy course objectives and assessments and demonstrated the usefulness of alignment assessment as a tool for continuous quality improvement.